Pengaruh Faktor Geografis Terhadap Kunjungan Antenatal Care di Klinik dr. Henny Chaerani Lebak Banten Tahun 2025 - Elfira Sri Futriani; Maria Adelgonda Oki (Universitas Pahlawan Tuanku Tambusai, 2025)
Routine pregnancy checks are very important for women during pregnancy. Several factors that influence antenatal care visits include knowledge, economics, socio-culture, geography (distance from residence), attitudes, information and access to services. In urban areas, access to ANC is generally easier than in rural areas, where distance is the main obstacle.To determine the influence of geographical factors on antenatal care visits at the Dr Henny Chaerani Clinic Lebak Banten.This research uses quantitative descriptive research with a cross sectional study approach, the sample in this study was 40 pregnant women, chi square statistical analysis test.There is an influence of geographical factors on antenatal care visits with a value of p=0.001.It is important for pregnant women to have regular health checks to monitor the progress of their pregnancy and get support. All pregnant women, whether near or far from a health facility, have the same opportunity to undergo an ANC (Antenatal Care) examination.